Reforming the governance of the IMF and the World Bank / edited by Ariel Buira - Buira, Ariel (ed.) (London, 2005)
Sixty years after their creation, the Bretton Woods institutions face a crisis of legitimacy that impairs their credibility and effectiveness. At the roots of this crisis lies the unrepresentative nature of their structure of governance, which places control of the institutions in the hands of a small group of industrial countries that do not use its resources. Developing countries and economies in transition are considered to be minor partners, despite accounting for half of the world's output in real terms, most of the world's population and encompassing the most dynamic economies and the largest holders of international reserves. The quota formulas should reflect the size of the economies of members, i.e. their GDP, their exposure to trade and capital movements as well as their ability to contribute to the Fund. If IMF quotas were based on objective measures, i.e. size of GDP, the volatility of receipts, the adjustment of European quotas for intra-trade and trade in a single currency in the euro area, the quota share of developing countries and economies in transition as a group should be no less than that of industrial countries. Reality has outpaced the evolution of thinking on the subject of governance. The growing breach between world economic and financial realities and the governance structure of the Bretton Woods institutions argues for reforms to increase the effectiveness and restore the legitimacy of these institutions. As debtors, the European countries had resisted conditionality during the first decades of the IMF and favoured increasing Fund resources, but as their situation changed, they no longer resorted to IMF support and they changed their position. Similar problems appear in the World Bank, giving rise to large negative flows of resources from the developing countries. The papers included in this book cover different aspects of the governance of the Bretton Woods institutions. They explore different options for reform and show that enhancing the participation of developing and emerging market countries in resolving the major monetary and financial problems confronting the world economy, would improve global economic performance and contribute to the elimination of world poverty. The papers included in this book cover different aspects of the governance of the Bretton Woods institutions. They explore different options for reform and show that enhancing the participation of developing and emerging market countries in resolving the major monetary and financial problems confronting the world economy, would improve global economic performance and contribute to the elimination of world poverty.
Keywords: World bank